Bio-inspired Coral-like Sensor Aiming at Ocean Wave Monitoring - Wang, Xinyu; Xu, Peng; Liu, Jianhua; Wang, Tingyu; Wang, Siyuan; Guan, Tangzhen; Liu, Xiangyu; Chen, Tianyu; Zheng, Jiaxi; Tao, Jin; Xu, Minyi (Chinese Automation Congress (Online), 2021)
Since designing efficient ocean wave sensors for marine engineering is still a challenge, in this paper, a self-powered bionic coral wave sensor (BCWS) based on a triboelectric nanogenerator (TENG) is proposed, which aims at wave detection for marine engineering construction, marine resource development, and marine disaster warning. The BCWS consists of coral tentacles, buoyancy disc, spring, counterweight mechanism, and perceiving units (60mm in length, 10mm in width, and 1.5mm in thickness) with multi-modal motions and encapsulates inside the coral tentacles through flexible rubber joints. Meanwhile, the unique structure of BCWS can not only eliminate the influence of seawater on the sensor output performance but also realize the three-dimensional perception of wave information. The analysis of experimental data reveals that BCWS perceive wave direction, wave height, wave frequency, and wave period with millimeter accuracy. Therefore, this novel BCWS can provide an intelligent solution for modern marine engineering.